GROWTH Framework: A Model for Human Capital Development in Tourism Through Vocational Higher Education - Andar Danova Lastaripar Goeltom; Eko Susanto; Anwari Masatip; Herry Rachmat Widjaja; Ali Muhtasom (Journal of Tourism, Hospitality and Travel Management, 2025)
In the face of evolving demands in the tourism sector, vocational higher education plays a strategic role in developing industry-ready human capital and empowerment to contribute to community-based sustainable tourism. This study proposes and validates the GROWTH Framework, a multi-theoretical model integrating Human Capital Theory, Stakeholder Theory, the Triple Helix Model, and Experiential Learning. The framework explores how curriculum quality, institutional support, contextual learning, and stakeholder participation affect graduate readiness, empowerment outcomes, and tourism ecosystem sustainability. Data were collected from 210 respondents, including vocational students, alumni, educators, and tourism village practitioners across several Indonesian provinces. All nine hypotheses were supported using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that experiential and context-specific learning significantly enhances graduate readiness and empowerment, while institutional and cross-sectoral collaboration fosters stakeholder participation and sustainable outcomes. This research contributes to the theoretical enrichment of vocational education discourse and offers practical recommendations for policymakers, educational institutions, and local tourism stakeholders. When strategically implemented, vocational tourism education catalyzes empowerment, innovation, and long-term sustainability in rural tourism ecosystems.